Survey on caching approaches in information centric networking - Abdullahi, Ibrahim; Che Mohamed Arif, Ahmad Suki; Hassan, Suhaidi (Elsevier B.V., 2015)
Information Centric Network (ICN) is increasingly becoming the alternative paradigm to the traditional Internet through improving information (content) dissemination on the Internet with names.The need to reduce redundancy and frequent access to a host (provider of information) has raised an alternative of a man-in-middle concept of ICN.This has necessitated the introduction of some ICN popular architectures (such as Named Data Network (NDN), Content Centric Network (CCN), to name a few) to manage the salient advantages incorporated in ICN.Despite all efforts and issues in naming, security, routing and mobility, power consumption; caching has become the leading variable to fully actualize the future Internet dream by carefully solving the problems in frequency and recency (in objects).Determining what part of the content is to be cached? When is the most appropriate time for caching? How would the object be cached (placed and replaced) and also what path would the object be cached? Thus, this paper span through some selected ICN architectures and projects to investigate and suggest forms of caching in minimizing the total bandwidth consumption, enhanced Delivery of Service (DoS), reduced upwards and downward streaming.In conclusion, pointing out some of the future probable ways to improve caching in ICN. This survey also highlighted the top sensitive issues that influence the active deployment of caches in ICN through recency, frequency, content size, cost of retrieval and coordination, update in caches and replacements. Several cache characteristics were further presented in ways that would improve cache techniques, deployments as research suggestions for content placement, replacement and quick scan on nodes on and off-path of the network.